Determinan Kinerja Personil Kepolisian di Polresta Tanjungpinang Kepulauan Riau - Hamdani Sitohang, Rifi; Langgeng Ratnasasi, Sri; Pintor Siolemba Patiro, Shine (Program Studi Manajemen FEBM UMRAH, 2025)
This study aims to analyze the influence of leadership style, organizational commitment, work motivation, and work-life balance on personnel performance at Tanjungpinang Police Resort. The research employed a quantitative method with data collection through questionnaires distributed to 200 non-commissioned officers. Data analysis was conducted using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The results showed that leadership style, organizational commitment, work motivation, and work-life balance had positive and significant effects on personnel performance. The research model indicating that 96.4% of the variation in personnel performance could be explained by these four independent variables. Organizational commitment had the strongest influence on performance, followed by work-life balance, leadership style, and work motivation. These findings provide important implications for developing strategies to improve police personnel performance through strengthening organizational commitment and work-life balance, as well as developing effective leadership styles and appropriate motivation systems.